Dynamics of a Discretization Physiological Control System - Xiaohua Ding; Huan Su (Discrete Dynamics in Nature and Society)
We study the dynamics of solutions of discrete physiological control system obtained by Midpoint rule. It is shown that a sequence of Hopf bifurcations occurs at the positive equilibrium as the delay increases and we analyze the stability of the solution of the discrete system and calculate the direction of the Hopf bifurcations. The numerical results are presented.